Peran Islam dalam Pengobatan Melayu: Penelitian - Choirun Niswah; Viona Dhea Az-Zahra; Alfin Saputra; Aulia Rahmadani; Nur Istikomah (Jurnal Pengabdian Masyarakat dan Riset Pendidikan, 2025)
This piece explores the important function of ulama, or Islamic scholars, within Malay medicine, which fuses spiritual beliefs with medical practices to support community health. As pivotal figures in Malay society, ulama take a comprehensive view that combines prayer, ruqyah, which involves spiritual cleansing, and the use of age-old herbal treatments handed down over time. The research illustrates that ulama serve not just as spiritual guides but also as advocates for public health, bridging traditional spiritual healing with contemporary medical approaches. In the context of Malay culture, this role creates a synergy between community faith in spirituality and the credibility attributed to scientific medicine. Additionally, this article examines how ulama help preserve local cultural traditions while also fostering the growth of health practices that are inclusive and community-oriented. By highlighting the blending of spiritual and medical aspects, the ulama's position is seen as vital for enhancing harmony and ensuring the ongoing viability of holistic health within Malay culture. This study seeks to offer fresh perspectives on the significance of a multidisciplinary approach to understanding traditional healing methods that continue to be significant today.